A shear-resistant fiber metal laminate and a preparation method thereof

By adopting a layering solution of surface-treated stainless steel extremely thin strip, carbon fiber braided fabric and unidirectional carbon fiber prepreg in the fiber metal layer, and combining nanomodified epoxy resin and carbon nanotube reinforced interface, the problem of layering damage in the fiber metal layer plate is solved, significantly improving its shear resistance and structural safety.

CN119590045BActive Publication Date: 2025-04-11TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510142033.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-11
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

Existing fiber metal laminates are prone to stratification damage under shear load, resulting in threats to structural integrity and safety.

Method used

The surface-treated stainless steel extremely thin strip, carbon fiber braided fabric and unidirectional carbon fiber prepreg were laid according to a specific laying scheme, and nanomodified epoxy resin was coated between the adjacent two layers, enhancing interface bonding through the pull-out and bridging mechanism of the carbon nanotubes.

Benefits of technology

The shear resistance of the fiber metal layer plate is improved, and the shear strength is increased by 17.4%, which enhances the energy absorption capacity of the material, reduces damage propagation, and thus improves the safety and service life of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119590045B_ABST
    Figure CN119590045B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of fiber metal laminates, and specifically discloses a shear-resistant fiber metal laminate and a preparation method thereof. Stainless steel ultra-thin strip, carbon fiber woven cloth, unidirectional carbon fiber prepreg are mixed according to [W / [G / 0 / G / 90] 2 / G c ] s The plying scheme is used for plying, and modified epoxy resin is coated between every two layers during the plying process, and a shear-resistant fiber metal laminate is obtained after curing; wherein W represents carbon fiber woven cloth, G represents stainless steel ultra-thin strip, 0 represents unidirectional carbon fiber prepreg laid at 0°, 90 represents unidirectional carbon fiber prepreg laid at 90°, Gc represents the center layer, s represents symmetrical plying along the center layer, and 2 represents the number of repetitions of [G / 0 / G / 90]. The shear-resistant fiber metal laminate prepared by the present invention greatly improves the shear resistance of the fiber metal laminate, and reduces the possibility of damage such as delamination damage, matrix rupture, fiber breakage, and metal plastic deformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fiber metal laminates, and in particular to a shear-resistant fiber metal laminate and a preparation method thereof. Background Art

[0002] FML (Fiber Metal laminates) is a composite material composed of metal and fiber materials, which has the performance advantages of metal materials and fiber materials. They have excellent corrosion resistance, high damage tolerance and high strength-to-weight ratio. Existing FMLs mainly include aramid reinforced aluminum alloy laminates (ARALL), glass reinforced aluminum alloy laminates (GLARE) and carbon reinforced aluminum alloy laminates (CARALLs), which are mainly used in aircraft structural parts such as aircraft skins, engine fairings, propeller blades, radar covers, etc. The bridging effect can produce a crack closure effect and inhibit crack propagation. Compared with other fibers, the bridging effect of aramid fibers is weaker, resulting in faster crack propagation speed of ARALLs in engineering applications and prone to premature failure. Due to its high density, GLARE boards are difficult to meet the weight reduction requirements of aviation structures. CARALLs are more susceptible to specific environmental factors, such as galvanic corrosion or degradation. Carbon fiber epoxy composites have good electrical conductivity and high electrode potential, which is generally higher than most metals. When it is combined with some metals with negative electrode potential (such as aluminum), the corrosion rate of the metal is significantly accelerated, causing significant damage in a short period of time. Therefore, with the continuous improvement of the performance requirements for aviation structural materials, researchers are increasingly focusing on finding metal materials with better comprehensive performance to overcome the limitations of the above-mentioned laminates. The addition of stainless steel (SS) to FML has excellent corrosion resistance, improves bending and tensile strain, and ultimately improves mechanical properties, making FML more widely used in complex designs and high-load conditions. Its excellent performance has promoted the development of new high-performance composite materials and provided new design options and material choices for the development of FML. In recent years, many scholars have conducted extensive research on the performance of FML containing ultra-thin stainless steel strips.

[0003] As a component of aircraft structure, FML is often subjected to loads such as bending, impact, shear, tension / compression, etc., resulting in a variety of failure modes. Common failure modes include delamination, matrix cracking, fiber breakage, and metal plastic deformation. For FML, due to the presence of a large number of fiber / metal interfaces inside it, delamination damage is prone to occur under the action of shear loads, causing FML to lose its bearing capacity and be severely damaged. Delamination damage is prone to occur under shear loads, posing a serious threat to the integrity and safety of the structure. Therefore, it is crucial to study the interfacial shear properties of FML because it has an important influence on the load transfer inside the laminate. Stronger interface bonding can enhance the energy absorption capacity of the material and reduce damage propagation, thereby improving the safety and service life of the structure. Summary of the invention

[0004] In view of this, the present invention provides a shear-resistant fiber metal laminate and a preparation method thereof to solve the problems of the existing fiber metal laminate being prone to delamination damage, matrix cracking, and structural integrity damage.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A method for preparing a shear-resistant fiber metal laminate comprises the following steps:

[0007] The surface treated stainless steel ultra-thin strip, carbon fiber woven cloth, and unidirectional carbon fiber prepreg were prepared according to [W / [G / 0 / G / 90]2 / G c ] s The plying scheme is used for plying, during which nano-modified epoxy resin is coated between two adjacent layers, and after curing, a shear-resistant fiber metal laminate is obtained;

[0008] Among them, W represents carbon fiber woven cloth, G represents surface-treated stainless steel ultra-thin strip, 0 represents unidirectional carbon fiber prepreg laid at 0°, 90 represents unidirectional carbon fiber prepreg laid at 90°, Gc represents the center layer, and s represents symmetrical laying along the center layer.

[0009] Preferably, the preparation method of the nano-modified epoxy resin comprises:

[0010] The epoxy resin, the diluent, the carbon nanotubes and the curing agent are mixed to obtain the nano-modified epoxy resin.

[0011] Preferably, the mass ratio of the epoxy resin, the diluent and the curing agent is 10:1.2-1.3:8-10; and the added amount of the carbon nanotubes in the nano-modified epoxy resin is 0.1-1wt.%.

[0012] Preferably, the coating amount of the modified epoxy resin applied between two adjacent layers during the lamination process is independently 2.22×10 -4 ~4.44×10-4 g / mm 2 .

[0013] Preferably, the curing includes a first curing and a second curing performed sequentially;

[0014] The temperature of the first curing is 120-125°C, the time of the first curing is 2-2.5h, and the pressure of the first curing is 0.70-0.75 MPa;

[0015] The temperature of the second curing is 160-165° C., the time of the second curing is 4-4.5 h, and the pressure of the second curing is 0.70-0.75 MPa.

[0016] Preferably, the method for preparing the surface-treated stainless steel ultra-thin strip is: polishing the surface of the stainless steel ultra-thin strip, immersing it in an alkaline solution for treatment, and obtaining the surface-treated stainless steel ultra-thin strip.

[0017] Preferably, the method for preparing the surface-treated stainless steel ultra-thin strip is: immersing the stainless steel ultra-thin strip in an alkali solution for pretreatment, and immersing the stainless steel ultra-thin strip in an acidic potassium dichromate solution for treatment after the pretreatment to obtain the surface-treated stainless steel ultra-thin strip.

[0018] Preferably, the preparation method of the surface-treated stainless steel ultra-thin strip is: mixing a silane coupling agent with an acidic alcohol solution to obtain an acidic modifier; immersing the stainless steel ultra-thin strip in the acidic modifier for treatment to obtain the surface-treated stainless steel ultra-thin strip.

[0019] Preferably, the carbon fiber woven cloth is 3238A-CF3052 carbon fiber woven cloth; and the unidirectional carbon fiber prepreg is T700 unidirectional carbon fiber prepreg.

[0020] Another object of the present invention is to provide a method for preparing a shear-resistant fiber metal laminate and to obtain a shear-resistant fiber metal laminate.

[0021] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:

[0022] The fiber metal laminate of the present invention is composed of a surface treated stainless steel ultra-thin strip, a carbon fiber woven cloth, and a unidirectional carbon fiber prepreg in the order of [W / [G / 0 / G / 90]2 / G c ] s The plying scheme is used for plying preparation. Through specific plying and the interaction between plying and nano-modified epoxy resin, the fiber metal laminate prepared by the present invention is not prone to delamination damage under shear load, and the integrity and safety of the structure can be ensured. It has strong interface bonding, can enhance the energy absorption capacity of the material, and reduce damage propagation, thereby improving the safety and service life of the structure.

[0023] The present invention adds nano-modified epoxy resin to the fiber metal laminate, which improves the shear resistance of the fiber metal laminate, and its shear strength is improved by 17.4%. When the nano-modified epoxy resin containing carbon nanotubes is selected, the carbon nanotubes can form a better mechanical anchoring between the metal layer and the polymer matrix, and enhance the interface bonding strength. Through the pull-out and bridging mechanism of the carbon nanotubes, the interface adhesion can be effectively improved, thereby improving the overall interlayer shear performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 The effects of different carbon nanotube content on the mechanical properties of modified epoxy resin are shown in Figure 2. Figure 1 (a) is a tensile stress-strain curve of nano-modified epoxy resin with different carbon nanotube doping amounts, (b) is a tensile stress bar graph of nano-modified epoxy resin with different carbon nanotube doping amounts, (c) is a bending stress-strain curve of nano-modified epoxy resin with different carbon nanotube doping amounts, and (d) is a bending strength bar graph of nano-modified epoxy resin with different carbon nanotube doping amounts;

[0026] Figure 2 The sample deformation diagram and finite element simulation deformation cloud diagram of the interlaminar shear failure test of Example 3 and Comparative Example 1 are shown in FIG. Figure 2 (a) in the figure corresponds to proportion 1, Figure 2 (b) corresponds to Example 3;

[0027] Figure 3 The interlaminar shear failure test results of Example 3 and Comparative Example 1 are as follows: Figure 3 (a) is the contact force-displacement curve of the interlayer shear test. Figure 3 (b) is the interlaminar shear strength bar graph;

[0028] Figure 4 This is a scanning electron microscope image of the fiber metal laminate prepared in Comparative Example 1. Figure 4 a in the figure corresponds to the microstructure at 1 μm scale. Figure 4 b in the figure corresponds to the microstructure at the scale of 200 nm;

[0029] Figure 5 This is a scanning electron microscope image of the fiber metal laminate prepared in Example 3. Figure 5a in the figure corresponds to the microstructure at 1 μm scale. Figure 5 b in the figure corresponds to the microstructure at the scale of 200 nm;

[0030] Figure 6 The three-point bending test results of Examples 1 to 3 are as follows: Figure 6 (a) is the contact force-displacement curve of the three-point bending test. Figure 6 (b) is the bending strength bar graph;

[0031] Figure 7 The strain field (εxy) analysis diagram of the three-point bending test at the beginning of loading, the beginning of damage and the peak of loading in Example 3;

[0032] Figure 8 The strain field (εxy) analysis diagram of the three-point bending test at the beginning of loading, the beginning of damage and the peak of loading in Example 2;

[0033] Fig. 9 This is an analysis diagram of the strain field (εxy) at the beginning of loading, the beginning of damage and the peak of loading in the three-point bending test of Example 1. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a shear-resistant fiber metal laminate, comprising the following steps:

[0035] The surface treated stainless steel ultra-thin strip, carbon fiber woven cloth, unidirectional carbon fiber prepreg were made according to [W / [G / 0 / G / 90]2 / G c ] s The plying scheme is used for plying, during which nano-modified epoxy resin is coated between two adjacent layers, and after curing, a shear-resistant fiber metal laminate is obtained;

[0036] Among them, W represents carbon fiber woven cloth, G represents surface-treated stainless steel ultra-thin strip, 0 represents unidirectional carbon fiber prepreg laid at 0°, 90 represents unidirectional carbon fiber prepreg laid at 90°, Gc represents the center layer, and s represents symmetrical laying along the center layer.

[0037] In the present invention, 0° and 90° are laying angles. 0° unidirectional carbon fiber prepreg means that the carbon fibers are arranged along the main loading direction of the composite material, which makes the material have the highest strength and stiffness in this direction. 90° unidirectional carbon fiber prepreg means that the carbon fibers are arranged perpendicular to the main loading direction, which can improve the performance of the composite material perpendicular to the loading direction and enhance its anisotropy and impact resistance.

[0038] In the present invention, the [W / [G / 0 / G / 90]2 / G c ] sThe specific laying plan is [W / G / 0 / G / 90 / G / 0 / G / 90 / G / 90 / G / 0 / G / 90 / G / 0 / G / W].

[0039] In the present invention, the preparation method of the nano-modified epoxy resin comprises:

[0040] The epoxy resin, the diluent, the carbon nanotubes and the curing agent are mixed to obtain the nano-modified epoxy resin.

[0041] In the present invention, the mass ratio of the epoxy resin, the diluent and the curing agent is 10:1.2~1.3:8~10, preferably 10:1.25:9; the added amount of carbon nanotubes in the nano-modified epoxy resin is 0.1~1wt.%, specifically 0.2wt.%, 0.4wt.%, 0.5wt.%, 0.6wt.%, 0.7wt.%, 0.8wt.%, 0.9wt.%, and most preferably 0.5wt.%.

[0042] In the present invention, the epoxy resin is preferably MF-4101 epoxy resin; the diluent is preferably one or more of 1,4-butanediol diglycidyl ether, phenyl glycidyl ether, dibutyl phthalate, styrene and toluene; the curing agent is preferably one or more of methyltetrahydrophthalic anhydride, ethylenediamine, triethylenetetramine, m-phenylenediamine, maleic anhydride and phthalic anhydride.

[0043] In the present invention, the mixing order of epoxy resin, diluent, carbon nanotubes and curing agent is preferably to mix epoxy resin and diluent first, and then add carbon nanotubes and curing agent to mix. The mixing temperature of epoxy resin and diluent is preferably 70°C, and the mixing temperature after adding carbon nanotubes and curing agent is preferably 60°C.

[0044] In the present invention, the coating amount of the modified epoxy resin applied between two adjacent layers during the lamination process is independently 2.22×10 -4 ~4.44×10 -4 g / mm 2 , specifically 2.4×10 -4 g / mm 2 , 2.5×10 -4 g / mm 2 , 2.8×10 -4 g / mm 2 , 3×10 -4 g / mm 2 , 3.2×10 -4 g / mm 2 , 3.5×10 -4 g / mm 2 , 3.8×10 -4 g / mm 2, 4×10 -4 g / mm 2 4.2×10 -4 g / mm 2 .

[0045] In the present invention, the curing includes a first curing and a second curing performed sequentially.

[0046] In the present invention, the temperature of the first curing is 120-125°C, specifically 120°C, 121°C, 122°C, 123°C, 124°C, 125°C; the time of the first curing is 2-2.5h, specifically 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h; the pressure of the first curing is 0.70-0.75 MPa, specifically 0.70 MPa, 0.71MPa, 0.72MPa, 0.73MPa, 0.74MPa, 0.75MPa; the temperature of the second curing is 160-165°C, specifically 160°C, 161°C, 162°C, 163°C, 164°C, 165°C; the time of the second curing is 4-4.5h, specifically 4h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h; the pressure of the second curing is 0.70-0.75 MPa, specifically 0.70 MPa, 0.71MPa, 0.72MPa, 0.73MPa, 0.74MPa, 0.75MPa.

[0047] In the present invention, the preparation method of the surface-treated stainless steel ultra-thin strip is: grinding the surface of the stainless steel ultra-thin strip, immersing it in alkali solution for treatment, and obtaining the surface-treated stainless steel ultra-thin strip; the purpose of grinding is to make the surface of the stainless steel ultra-thin strip rough and clean, without special limitation; the alkali solution includes sodium hydroxide solution and / or potassium hydroxide solution; the mass concentration of the alkali solution is preferably 8-15%, specifically 9%, 10%, 12%, 14%; the treatment time is preferably 1.5-2.5h, specifically 1.8h, 2h, 2.2h, 2.4h.

[0048] In the present invention, the preparation method of the surface-treated stainless steel ultra-thin strip is as follows: immersing the stainless steel ultra-thin strip in an alkali solution for pretreatment, and immersing the stainless steel ultra-thin strip in an acidic potassium dichromate solution for treatment after the pretreatment is completed to obtain the surface-treated stainless steel ultra-thin strip; the alkali solution includes a sodium hydroxide solution and / or a potassium hydroxide solution, and the molar concentration of the alkali solution is preferably 0.03-0.07 mol / L, specifically 0.04 mol / L, 0.05 mol / L, 0.06 mol / L; the pretreatment temperature is preferably 50-70°C, specifically 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C; the pretreatment time is preferably 4~6min, specifically 4.2min, 4.5min, 4.8min, 5min, 5.2min, 5.5min, 5.8min; the acidic potassium dichromate solution is preferably prepared by mixing a K2Cr2O7 solution with a diluted H2SO4 solution, and the mass concentration of the K2Cr2O7 solution is preferably 30~40g / L, preferably 35g / L; the mass concentration of the H2SO4 solution is preferably 320~380g / L, preferably 350g / L; the treatment temperature is 50~70°C, preferably 60°C; the treatment time is 40~50min, and most preferably 45min.

[0049] In the present invention, the preparation method of the surface-treated stainless steel ultra-thin strip is: mixing a silane coupling agent with an acidic alcohol solution to obtain an acidic modifier; immersing the stainless steel ultra-thin strip in the acidic modifier for treatment to obtain the surface-treated stainless steel ultra-thin strip; the volume ratio of the silane coupling agent, deionized water and alcohol in the acidic modifier is 3~8:3~8:80~100, and the most preferred ratio is 5:5:90; the alcohol is preferably ethanol; the acidic alcohol solution is preferably adjusted to a pH value of acetic acid, and the pH value of the acidic alcohol solution is preferably 3~5, and the most preferred ratio is 4; the treatment time is preferably 25~35min, and the most preferred ratio is 30min.

[0050] In the present invention, when the surface treatment of the stainless steel ultra-thin strip is performed by the acidic potassium dichromate method, the surface treatment effect is better than that by the method of using a silane coupling agent, the contact angle is reduced by 7.7%, and the bending strength is increased by 6%. It can effectively change the polarity of the surface of the stainless steel ultra-thin strip, thereby improving the compatibility of the metal and the polymer matrix. This improvement in compatibility helps to reduce interface debonding and improve durability, and improve the overall mechanical properties of the FML. The acidic potassium dichromate method corrodes the surface of the stainless steel ultra-thin strip, increases the surface roughness of the stainless steel ultra-thin strip, and the resin at high temperature flows into the surface of the stainless steel ultra-thin strip, forming a "mechanical locking" effect. This method has a greater improvement in the shear resistance of the FML.

[0051] In the present invention, the carbon fiber woven cloth is 3238A-CF3052 carbon fiber woven cloth; and the unidirectional carbon fiber prepreg is T700 unidirectional carbon fiber prepreg.

[0052] The present invention also provides a method for preparing a shear-resistant fiber metal laminate and a shear-resistant fiber metal laminate prepared therefrom.

[0053] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] First, weigh MF-4101 epoxy resin in a beaker, then drop 1,4-butanediol diglycidyl ether diluent (mix the epoxy resin and the diluent in a mass ratio of 8:1) and stir evenly at 70°C, then add 0.5%wt of CNTs and methyltetrahydrophthalic anhydride curing agent (mix the epoxy resin and the curing agent in a mass ratio of 10:9) into the beaker and stir evenly at 60°C to obtain nano-modified epoxy resin for later use.

[0056] The stainless steel ultra-thin strip (ASIS 304, thickness 0.1 mm, Taiyuan Iron and Steel Co., Ltd.) was immersed in a 0.5 mol / L NaOH solution at a temperature of 60°C for 5 min to form a black layer on the metal surface. Then, it was placed in a FPL solution at a temperature of 60°C for 45 min (FPL solution: K2Cr2O7 solution (35 g potassium dichromate plus 1 L deionized water) and diluted H2SO4 solution (350 g sulfuric acid plus 1 L deionized water) were mixed to prepare). Finally, it was immersed in distilled water for washing to remove the residual solution to obtain a surface-treated stainless steel ultra-thin strip for use.

[0057] According to [W / [G / 0 / G / 90]2 / G c ] s The plying scheme is to ply G-stainless steel ultra-thin strip (surface treated stainless steel ultra-thin strip), W-carbon fiber woven cloth (3238A-CF3052 carbon fiber woven cloth), and unidirectional carbon fiber prepreg (T700 unidirectional carbon fiber prepreg). The modified epoxy resin is applied between each adjacent layer, and the coating amount between each two layers is 2.22×10 -4 g / mm 2 After the ply was completed, it was cured at 120°C for 2 hours and then at 160°C for 4 hours, wherein the curing pressure was 0.7 MPa, and a shear-resistant fiber metal laminate with a thickness of 2.55 mm was obtained, which was recorded as S6.

[0058] Example 2

[0059] First, weigh MF-4101 epoxy resin in a beaker, then drop 1,4-butanediol diglycidyl ether diluent (mix the epoxy resin and the diluent in a mass ratio of 8:1) and stir evenly at 70°C, then add 0.5%wt of CNTs and methyltetrahydrophthalic anhydride curing agent (mix the epoxy resin and the curing agent in a mass ratio of 10:9) into the beaker and stir evenly at 60°C to obtain nano-modified epoxy resin for later use.

[0060] Deionized water and ethanol were mixed, acetic acid was added to adjust the pH value to 4, A-187 silane coupling agent, deionized water and ethanol were added in a volume ratio of 5:5:90 to hydrolyze silane, and then stainless steel ultra-thin sheets (ASIS 304, thickness 0.1 mm, Taiyuan Iron and Steel Co., Ltd.) were added. Ultrasonic oscillation was performed for 30 minutes, and finally, it was dried with cold air to obtain a surface-treated stainless steel ultra-thin strip for use.

[0061] According to [W / [G / 0 / G / 90]2 / G c ] s The plying scheme is to ply G-stainless steel ultra-thin strip (surface treated stainless steel ultra-thin strip), W-carbon fiber woven cloth (3238A-CF3052 carbon fiber woven cloth), and unidirectional carbon fiber prepreg (T700 unidirectional carbon fiber prepreg). The modified epoxy resin is applied between each adjacent layer, and the coating amount between each two layers is 2.22×10 -4 g / mm 2 After the ply was completed, it was cured at 120°C for 2 hours and then at 160°C for 4 hours, wherein the curing pressure was 0.7 MPa, and a shear-resistant fiber metal laminate with a thickness of 2.55 mm was obtained, which was recorded as S5.

[0062] Example 3

[0063] First, weigh MF-4101 epoxy resin in a beaker, then drop 1,4-butanediol diglycidyl ether diluent (mix the epoxy resin and the diluent in a mass ratio of 8:1) and stir evenly at 70°C, then add 0.5%wt of CNTs and methyltetrahydrophthalic anhydride curing agent (mix the epoxy resin and the curing agent in a mass ratio of 10:9) into the beaker and stir evenly at 60°C to obtain nano-modified epoxy resin for later use.

[0064] Firstly, the surface of the stainless steel ultra-thin strip (ASIS 304, thickness 0.1 mm, Taiyuan Iron and Steel Co., Ltd.) was polished to make its surface rough and clean, and then the surface of the stainless steel ultra-thin strip was cleaned with acetone solution to remove dust, rust, grease, etc. on its surface; it was immersed in 10% sodium hydroxide solution for 2 h, and then the treated stainless steel ultra-thin strip was placed in a drying oven for drying.

[0065] According to [W / [G / 0 / G / 90]2 / G c ] s The plying scheme is to ply G-stainless steel ultra-thin strip (surface treated stainless steel ultra-thin strip), W-carbon fiber woven cloth (3238A-CF3052 carbon fiber woven cloth), and unidirectional carbon fiber prepreg (T700 unidirectional carbon fiber prepreg). The modified epoxy resin is applied between each adjacent layer, and the coating amount between each two layers is 2.22×10 -4 g / mm 2 After the ply was completed, it was cured at 120°C for 2 hours and then at 160°C for 4 hours, wherein the curing pressure was 0.7 MPa, and a shear-resistant fiber metal laminate with a thickness of 2.55 mm was obtained, which was recorded as S4.

[0066] Example 4

[0067] First, weigh MF-4101 epoxy resin in a beaker, then drop phenyl glycidyl ether diluent (mix the epoxy resin and the diluent in a mass ratio of 10:1.2) and stir evenly at 70°C, then add 0.5%wt of CNTs and triethylenetetramine curing agent (mix the epoxy resin and the curing agent in a mass ratio of 10:8) into the beaker and stir evenly at 60°C to obtain nano-modified epoxy resin for later use.

[0068] The stainless steel ultra-thin strip (ASIS 304, thickness 0.1 mm, Taiyuan Iron and Steel Co., Ltd.) was immersed in a 0.5 mol / L NaOH solution at a temperature of 60°C for 5 min to form a black layer on the metal surface. Then, it was placed in a FPL solution at a temperature of 60°C for 45 min (FPL solution: K2Cr2O7 solution (35 g potassium dichromate plus 1 L deionized water) and diluted H2SO4 solution (350 g sulfuric acid plus 1 L deionized water) were mixed to prepare). Finally, it was immersed in distilled water for washing to remove the residual solution to obtain a surface-treated stainless steel ultra-thin strip for use.

[0069] According to [W / [G / 0 / G / 90]2 / G c ] s The layering scheme is to layer G-stainless steel ultra-thin strip (surface treated stainless steel ultra-thin strip), W-carbon fiber woven cloth (3238A-CF3052 carbon fiber woven cloth), and unidirectional carbon fiber prepreg (T700 unidirectional carbon fiber prepreg). The modified epoxy resin is coated between each adjacent layer, and the coating amount between each two layers is 3×10 -4 g / mm 2 After the ply was completed, it was cured at 125°C for 2.5 hours and then at 165°C for 4 hours, wherein the curing pressure was 0.72 MPa in both cases, to obtain a shear-resistant fiber metal laminate.

[0070] Example 5

[0071] First, weigh MF-4101 epoxy resin in a beaker, then drop phenyl glycidyl ether diluent (mix the epoxy resin and the diluent in a mass ratio of 10:1.3) and stir evenly at 70°C, then add 0.5%wt of CNTs and m-phenylenediamine curing agent (mix the epoxy resin and the curing agent in a mass ratio of 10:10) into the beaker and stir evenly at 60°C to obtain nano-modified epoxy resin for later use.

[0072] The stainless steel ultra-thin strip (ASIS 304, thickness 0.1 mm, Taiyuan Iron and Steel Co., Ltd.) was immersed in a 0.5 mol / L NaOH solution at a temperature of 60°C for 5 min to form a black layer on the metal surface. Then, it was placed in a FPL solution at a temperature of 60°C for 45 min (FPL solution: K2Cr2O7 solution (35 g potassium dichromate plus 1 L deionized water) and diluted H2SO4 solution (350 g sulfuric acid plus 1 L deionized water) were mixed to prepare). Finally, it was immersed in distilled water for washing to remove the residual solution to obtain a surface-treated stainless steel ultra-thin strip for use.

[0073] According to [W / [G / 0 / G / 90]2 / G c ] s The layering scheme is to layer G-stainless steel ultra-thin strip (surface treated stainless steel ultra-thin strip), W-carbon fiber woven cloth (3238A-CF3052 carbon fiber woven cloth), and unidirectional carbon fiber prepreg (T700 unidirectional carbon fiber prepreg). The modified epoxy resin is coated between each adjacent layer, and the coating amount between each two layers is 4.4×10 -4 g / mm 2 After the ply was completed, it was cured at 122°C for 2.5 hours and then at 160°C for 4.5 hours, wherein the curing pressure was 0.75 MPa in both cases, to obtain a shear-resistant fiber metal laminate.

[0074] Experimental Example 1

[0075] The addition amount of CNTs in the preparation process of the modified epoxy resin in Example 1 was adjusted to 0, 0.05%, 0.1%, 0.2%, 1%, and 2%wt of the total mass, respectively, to obtain a series of modified epoxy resins, which were tested for flexural strength and tensile strength together with the modified epoxy resin obtained in Example 1. The test results are shown in Figure 1 ;in, Figure 1 (a) is the tensile stress-strain curve of nano-modified epoxy resin with different carbon nanotube doping amounts, (b) is the tensile stress bar graph, (c) is the bending stress-strain curve, and (d) is the bending stress bar graph. Figure 1As can be seen from (a) in the figure, the maximum tensile stress is 10.92MPa when 0.5wt% carbon nanotubes are added. Figure 1 As can be seen from (b) in Figure 1, the maximum tensile strength is 67.86 MPa when 0.5 wt% carbon nanotubes are added. Figure 1 As can be seen from (c) in Figure 1, the maximum bending stress is 119 MPa when 0.5 wt% carbon nanotubes are added. Figure 1 As can be seen from (d) in the figure, the maximum bending strength is 119 MPa when 0.5 wt% carbon nanotubes are added. In summary, when 0.5 wt% carbon nanotubes are added, the bending and tensile properties of the modified epoxy resin are the best.

[0076] Comparative Example 1

[0077] The difference between this comparative example and Example 3 is that no CNTs are added to the modified epoxy resin as a binder, which is denoted as S1.

[0078] Experimental Example 2

[0079] The interlaminar shear failure test was performed on Example 3 and Comparative Example 1 respectively. The test method of the interlaminar shear test was as follows: the test was performed on an Instron 5969 test system with a maximum load capacity of 50 kN, and the ASTM D7264 standard was followed, with a loading speed of 1 mm / min. In addition, the radius of the indenter was 5.0 mm, the same as the support seat. Different support spans can be achieved by adjusting the distance between the support seats. The span-to-thickness ratio of 32:1 was selected in this experiment with reference to the standard. The test system can record the load-displacement curve of each specimen. To ensure the reliability of the final result, at least 3 tests were performed under the same bending condition.

[0080] The following formula is used to calculate the bending strength:

[0081] in: is the tensile strength (MPa), P is the maximum force (N) that the specimen withstands when it is broken. L is the support span (mm), b is the width of the specimen (mm), h is the thickness of the specimen (mm).

[0082] The deformation cloud diagram of the specimen is as follows: Figure 2 As shown, Figure 2 (a) in the figure corresponds to proportion 1, Figure 2 (b) in the embodiment corresponds to Example 3. Figure 2It can be seen that, compared with Example 3, Comparative Example 1 has a more obvious bending deformation and slippage occurs at the end of the specimen, while Example 3 only has a weak bending deformation and no shear slippage occurs at the end. The deformation cloud diagram shows that during the specimen test, the surface of the specimen is subjected to stress concentration, resulting in a large load, and then the stress gradually expands along the thickness direction. This proves from the side that the addition of carbon nanotubes improves the overall anti-interlayer shear performance of FML.

[0083] The interlaminar shear test was carried out on Example 3 and Comparative Example 1, and the experimental method was the same as above. The contact force-displacement curve after the test is as follows: Figure 3 As shown in (a) in the figure, the change of the curve is that the contact force increases linearly with the increase of displacement. When the contact force reaches the peak value, damage begins to appear inside the FML, and the contact force begins to decrease rapidly. Figure 3 From (a) in Example 3, it can be seen that the peak load of Example 3 is 1.81 kN, and the peak load of Comparative Example 1 is 1.54 kN. By calculating the interlaminar shear strength, ( Figure 3 In (b) of the figure, the interlaminar shear strength of Example 3 is 53.2 MPa, which is 17.4% higher than that of Comparative Example 1 (45.3 MPa). It can be concluded from the experimental results that the addition of carbon nano-modified epoxy resin between the fiber layer and the metal layer improves the interlaminar shear strength of the FML.

[0084] The sample morphologies of Comparative Example 1 and Example 3 were observed under a scanning electron microscope, and the mechanism of how CNTs improve the interlaminar shear performance of the fiber metal laminate was studied. Figure 4 a in the figure is the microstructure of comparative example 1 at a scale of 1 μm. Figure 4 b in the figure is the microstructure of comparative example 1 at a scale of 200 nm. Figure 5 a in the figure is the microstructure of Example 3 at a scale of 1 μm. Figure 5 b in the figure is the microstructure of Example 3 at a scale of 200 nm. Figure 4 As can be seen from a and b in the figure, the specimen without CNTs cannot suppress the formation of holes or cracks in the matrix, which eventually leads to rapid failure. Figure 5 From a and b in the figure, we can see that the addition of CNTs bridges the cracks in the matrix, inhibits the rapid expansion of the matrix cracks, and indirectly improves the overall shear resistance of the fiber metal laminate.

[0085] The FML specimens prepared in Examples 1 to 3 were subjected to interlaminar shear tests. The test method adopted a three-point bending test: the SBS test and the three-point bending test were performed using an Instron 5969 universal material testing machine with a maximum capacity of 50 kN. During the test, the loading head descent speed was set to 1 mm / min, the descent radius was 10 mm, and the descent radius of the support fixture was 10 mm. In order to better observe the shear failure process of the fiber metal laminate in the experiment, a high-speed camera was used to record the entire shear deformation failure process of the specimen. In order to ensure the accuracy of the test results, three identical SBS tests were performed on each type of fiber metal laminate. The contact force-displacement curve after the test is shown in the figure. Figure 6 As shown in (a) in the figure, the overall change trend of the curve is that the contact force increases linearly with the increase of displacement, and immediately decreases after reaching the peak value. After the three-point bending test of FML, the minimum contact force of Example 3 is 0.31 kN, and the contact forces of Example 2 and Example 1 are larger, 0.36 kN and 0.39 kN respectively. Figure 6 It can be seen from (b) that the maximum bending strength of Example 1 is 564.7MPa, which is 24.5% and 5.9% higher than that of Example 3 and Example 2, respectively. It can be seen that the use of the FPL method (corresponding to the stainless steel ultra-thin strip processing method in Example 1) and the SCA method (corresponding to the stainless steel ultra-thin strip processing method in Example 2) to surface treat the stainless steel ultra-thin strip enhances the bending strength of the FML, allowing it to withstand greater loads under the same conditions. Compared with the SCA method, the FPL method chemically corrodes the metal surface, increases the surface roughness, is more conducive to the mechanical locking phenomenon caused by resin infiltration, enhances the bonding effect between interfaces, and thus improves its interlayer shear performance.

[0086] The strain field (εxy) of the strain diagram at the beginning of loading, the beginning of damage and the peak of loading is analyzed. The analysis results are as follows: Figure 7~Figure 9 As shown ( Figure 7 , Figure 8 , Fig. 9Corresponding to Example 3, Example 2, and Example 1 respectively), negative values ​​indicate the compression direction, and positive values ​​indicate the tensile direction. In the strain distribution in the xy direction, the compressive strain under the action of the indenter load is the main distribution form, and the maximum strains of Example 3, Example 2, and Example 1 are 0.1818, 0.2526, and 0.7048, respectively. That is, the maximum strain first appears when the load is about 0.31kN, 0.36kN, and 0.39kN, and the FML begins to show interlayer delamination. When damage occurs, microcracks begin to expand, the strain concentration area increases, and the scattered points begin to move, resulting in partial loss of the strain field. When the peak load is reached, the cracks in the specimen begin to expand, and the spots fall off severely, indicating that the specimen has been severely damaged. It can be seen that when the contact force reaches the peak value, strain concentration begins to appear in Example 3, which indicates the occurrence of delamination damage. The strain of Example 3 is concentrated in the surface layer where the indenter contacts the FML, indicating that the delamination failure between the upper metal / prepreg layers causes the overall failure of the FML. The difference is that there is no strain concentration phenomenon in Example 2 and Example 1, indicating that under the same loading conditions, Example 2 and Example 1 produce smaller interlayer delamination damage, indicating that the FPL method (corresponding to the stainless steel ultra-thin strip processing method in Example 1) and the SCA method (corresponding to the stainless steel ultra-thin strip processing method in Example 2) are beneficial to reducing the interlayer delamination damage by performing surface treatment on the stainless steel ultra-thin strip.

[0087] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0088] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a shear-resistant fiber metal laminate, characterized in that: The steps include: The surface treated stainless steel ultra-thin strip, carbon fiber woven cloth, and unidirectional carbon fiber prepreg were prepared according to [W / [G / 0 / G / 90]2 / G c ] s The plying scheme is used for plying, during which nano-modified epoxy resin containing carbon nanotubes is coated between two adjacent layers, and after curing, a shear-resistant fiber metal laminate is obtained; Among them, W represents carbon fiber woven cloth, G represents surface treated stainless steel ultra-thin tape, 0 represents unidirectional carbon fiber prepreg laid at 0°, 90 represents unidirectional carbon fiber prepreg laid at 90°, and G represents c represents the center layer, s represents the symmetrical plying along the center layer, and 2 represents the number of repetitions of [G / 0 / G / 90]; The method for preparing the surface-treated stainless steel ultra-thin strip comprises: grinding the surface of the stainless steel ultra-thin strip, immersing the strip in an alkali solution for treatment, and obtaining the surface-treated stainless steel ultra-thin strip; and / or The stainless steel ultra-thin strip is immersed in an alkali solution for pretreatment, and after the pretreatment is completed, it is immersed in an acidic potassium dichromate solution for treatment to obtain a surface-treated stainless steel ultra-thin strip; and / or The silane coupling agent is mixed with an acidic alcohol solution to obtain an acidic modifier; the stainless steel ultra-thin strip is immersed in the acidic modifier for treatment to obtain a surface-treated stainless steel ultra-thin strip.

2. The method for preparing a shear-resistant fiber metal laminate according to claim 1, characterized in that: The preparation method of the nano-modified epoxy resin comprises: The epoxy resin, the diluent, the carbon nanotubes and the curing agent are mixed to obtain the nano-modified epoxy resin.

3. The method for preparing a shear-resistant fiber metal laminate according to claim 2, characterized in that: The mass ratio of the epoxy resin, the diluent and the curing agent is 10:1.2-1.3:8-10; the added amount of the carbon nanotubes in the nano-modified epoxy resin is 0.1-1wt.%.

4. The method for preparing a shear-resistant fiber metal laminate according to any one of claims 1 to 3, characterized in that: The coating amount of modified epoxy resin applied between two adjacent layers during the lamination process is 2.22×10 -4 ~4.44×10 -4 g / mm 2 .

5. The method for preparing a shear-resistant fiber metal laminate according to claim 4, characterized in that: The curing includes a first curing and a second curing performed sequentially; The temperature of the first curing is 120-125°C, the time of the first curing is 2-2.5h, and the pressure of the first curing is 0.70-0.75 MPa; The temperature of the second curing is 160-165° C., the time of the second curing is 4-4.5 h, and the pressure of the second curing is 0.70-0.75 MPa.

6. The method for preparing a shear-resistant fiber metal laminate according to claim 1, characterized in that: The carbon fiber woven cloth is 3238A-CF3052 carbon fiber woven cloth; the unidirectional carbon fiber prepreg is T700 unidirectional carbon fiber prepreg.

7. A shear-resistant fiber metal laminate prepared by the method for preparing a shear-resistant fiber metal laminate according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Modified epoxy resin base material and modified epoxy resin matrix composite material

    CN102617984A

  • Stainless steel / carbon fiber / stainless steel laminated plate rolling technology

    CN113183492A